Effectiveness of beta-tricalcium phosphate in comparison with other materials in treating periodontal infra-bony defects around natural teeth: a systematic review and meta-analysis - Reham AL Jasser; Abdulelah AlSubaie; Fayez AlShehri (BMC, 2021)
Abstract Background Beta-tricalcium phosphate in regenerative surgery has shown promising results in terms of bone gain and new vital bone formation; however, several studies have contradicted this finding. The aim of this study was to evaluate the effectiveness of beta-tricalcium phosphate compared to other grafting materials in the regeneration of periodontal infra-bony defects. Methods Electronic database (Cochrane, MEDLINE, PubMed, Embase, Science Citation Index Expanded) and manual searches for related data were performed up until March 2020. The outcomes were pocket depth reduction, clinical attachment level gain, and amount of bone fill. Results Five studies were selected based on the inclusion criteria. Bone regeneration with beta-tricalcium phosphate was observed to be superior to that with debridement alone but showed comparable results to other bone graft materials in terms of pocket depth reduction, clinical attachment level gain, and bone fill. Regenerative procedures for periodontal infra-bony defects that used beta-tricalcium phosphate in combination with other growth factors yielded superior outcomes. The meta-analysis revealed that for cases with two-wall defects, the use of beta-tricalcium phosphate yielded statistically significant differences in pocket depth reduction and clinical attachment level gain, but not in bone fill. Conclusions Beta-tricalcium phosphate appears to be a promising material for use in periodontal infra-bony defect regeneration around natural teeth. However, randomized clinical trials with larger sample sizes and more controlled study designs are needed to support these findings.